2020
DOI: 10.1007/s10433-020-00584-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards working in retirement: a latent class analysis of older workers’ motives

Abstract: One of the fastest growing labour market groups is working pensioners, meaning those who work past the statutory retirement age whilst receiving a pension. Previous research has investigated the motives of this group and found very heterogeneous reasons for employment in retirement. However, little is known about the expectations and preferred work arrangements of older workers regarding a potential post-retirement employment. Using data from the German survey transitions and old age potential, we explore olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The present article adds to previous knowledge on postretirement employment by showing that work-related motivational drivers predict not only the preference for ( Hess et al, 2021 ; van Solinge et al, 2021 ) and participation in ( Fasbender et al, 2016 ; Zhan et al, 2015 ) postretirement work, but also the extent to which retirees change their level of engagement over time. The finding that different motives have differential implications for changes in work extent improve our understanding of postretirement work in several important ways.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The present article adds to previous knowledge on postretirement employment by showing that work-related motivational drivers predict not only the preference for ( Hess et al, 2021 ; van Solinge et al, 2021 ) and participation in ( Fasbender et al, 2016 ; Zhan et al, 2015 ) postretirement work, but also the extent to which retirees change their level of engagement over time. The finding that different motives have differential implications for changes in work extent improve our understanding of postretirement work in several important ways.…”
Section: Discussionsupporting
confidence: 56%
“…Research confirms this assumption and shows that financial motives are important for understanding why retirees continue to work in retirement, although it has been shown to be less prevalent than social and personal motives ( Dingemans & Henkens, 2014 ; Hansson et al, 2020 ; Mazumdar et al, 2020 ; Platts et al, 2021 ). The financial meaning of work is suggested to be a stronger predictor of postretirement employment among retirees with poor economic status ( Fasbender et al, 2016 ), and financial motives are related to a preference to work more hours in retirement ( Hess et al, 2021 ). Research on older workers further demonstrates that many part-time jobs are involuntary, that older workers often want to work more, and that financial strain is one of the main motivators to increase work hours ( Silver et al, 2019 ; Starace et al, 2015 ; Van Horn & Heidkamp, 2019 ).…”
Section: Reasons For Working In Retirementmentioning
confidence: 99%
See 1 more Smart Citation
“…As Zhao et al (2018) looked at the financial risks of pension plans, they revealed that risk assessment of the Pension Plan system is critical to avoid shocks to the demographic structure and economic transition in old age. In some countries, there is a motive for post-retirement workers to continue working, which Hess et al (2021) describe as financially driven, status-driven, contact and pleasure-driven, and generatively driven. Furthermore, according to a study by Tao (2017) in Germany, the current pension system reform has become much more gender-neutral, 'feminine' and 'family-friendly, by balancing the pension rights of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Rising life expectancy and ageing baby boomers, potential strains on social security funds, pension reforms and labour-market changes are generating growing interest in the potential employment of older adult workers and retirees. Labour-market scholars study the prevalence and circumstances of employment in old age, adding relevant knowledge about older workers' expectations of working in retirement (Hess et al, 2021). As against the conventional perception and experience of retirement as the point at which one quits the labour market for good, many scholars today recommend that it be conceptualised as one stage in a gradual process (Bordia et al, 2020;Hasselhorn, 2020).…”
Section: Introductionmentioning
confidence: 99%